The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1128/mbio.02079-19
|View full text |Cite
|
Sign up to set email alerts
|

TpiA is a Key Metabolic Enzyme That Affects Virulence and Resistance to Aminoglycoside Antibiotics through CrcZ in Pseudomonas aeruginosa

Abstract: Carbon metabolism plays an essential role in bacterial pathogenesis and susceptibility to antibiotics. In Pseudomonas aeruginosa, Crc, Hfq, and a small RNA, CrcZ, are central regulators of carbon metabolism. By screening mutants of genes involved in carbon metabolism, we found that mutation of the tpiA gene reduces the expression of the type III secretion system (T3SS) and bacterial resistance to aminoglycoside antibiotics. TpiA is a triosephosphate isomerase that reversibly converts glyceraldehyde 3-phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Fragments of the promoter regions of the indicated genes were amplified by PCR with primers listed in Table S3 , using PA14 chromosomal DNA as the template. The PCR products were cloned into the Sma I- Hin dIII sites of the plasmid pUCP20- lacZ [ 36 ]. The resulting plasmid was transferred into the indicated strains.…”
Section: Methodsmentioning
confidence: 99%
“…Fragments of the promoter regions of the indicated genes were amplified by PCR with primers listed in Table S3 , using PA14 chromosomal DNA as the template. The PCR products were cloned into the Sma I- Hin dIII sites of the plasmid pUCP20- lacZ [ 36 ]. The resulting plasmid was transferred into the indicated strains.…”
Section: Methodsmentioning
confidence: 99%
“…The decrease in the metabolic fitness level may be due to the obstruction of oxidative phosphorylation and the accumulation of NADH, which reduce metabolic activity through feedback effects. In P. aeruginosa, the TpiA-mediated conversion between glyceraldehyde-3-phosphate (G3P) to dihydroxyacetone phosphate (DHAP) serves as a critical link between glycolysis and phospholipid synthesis [43]. The high expression of tpiA, gpsA, pgpA and cls also indicates the enhancement of phospholipid synthesis activity and the decrease of glucose metabolism.…”
Section: The Response Of P Aeruginosa To D-11 and Azithromycinmentioning
confidence: 99%
“…GpmA (putative hydrolase) and AtpB (ATP synthase subunit a) were associated with the glycolysis pathway and oxidative phosphorylation (Radin et al, 2019;Dominguez-Ramirez et al, 2020). TpiA (triosephosphate isomerase) may contribute to the uptake of extracellular matrixes including aminoglycoside and activate the process of energy production in oxidative phosphorylation, carbon metabolism, and respiration (Chen et al, 2017;Xia et al, 2020). In addition, McCloskey et al (2018) reported that deletion of tpiA led to a negative effect on the growth rate and glycolysis pathway in E. coli.…”
Section: Discussionmentioning
confidence: 99%